The effect of oxidising thermal exposures on the fatigue properties of a polycrystalline powder metallurgy nickel-based superalloy - David Lewis (Materials & Design, 2020)
A number of thermal exposures were undertaken to determine the effect oxidation has on the fatigue lives of the nickel-based superalloy RR1000. The thermal exposures initially caused a considerable reduction in the fatigue lives with increasing oxidation. However, the longest exposure time resulted in an S-N curve that lay between the shortest and mid length exposure. A range of analyses were undertaken to determine the presence of any mechanisms that could have caused this unexpected life increase; vacuum thermal exposures, small punch tensile, nanoindentation, microscopy and transmission Kikuchi diffraction. It was found that few of the mechanisms investigated were likely to have an effect on the change in life with the exceptions being; reduction in dislocation movement and crack deflection as a result of a recrystallised zone at the surface, variation in hardness of different regions due to a γ′ depleted plastic zone and a hard ceramic oxide, and reduced initiations due to the presence of a ‘healing’ chromium oxide scale. Notch fatigue tests were performed to determine the importance of the findings to components in service and it was found that the notch acted as the cause of crack initiation, effectively mitigating against the effects of the oxidation damage.